In the book of Karatzas and Shreve Brownian Motion and Stochastic Calculus on page 31, after Definition 5.5 (of the cross-variation-process $\langle X,Y\rangle$) they say: The uniqueness argument in the Doob-Meyer Decomposition also shows that $\langle X,Y\rangle$ is, up to indistinguishability, the only process of the form $A = A^{(1)} - A^{(2)}$ with $A^{(j)}$ adapted and natural increasing, such that $XY - A$ is a martingale.

I don't understand this. $XY$ is not necessarily a submartingale, so we can't apply the theorem directly. Assuming there would be another such decomposition $A = B - C$, then we do not have necessarily that $X - A$ or $X - B$ is a martingale, so we cannot apply the uniqueness argument. What am I missing here?

They define the cross-variation as $\langle X,Y\rangle = \frac{1}{4}[\langle X+Y\rangle - \langle X-Y\rangle]$ where $\langle Z\rangle$ is the unique process increasing, natural process, s.t. $Z^2 - \langle Z\rangle$ is a martingale (we get $\langle Z\rangle$ from the Doob-Meyer decomposition).


2 Answers 2


If $X$ and $Y$ are semimartingales you can use Ito's Lemma to write $$X_tY_t = X_0Y_0 + \int\limits_0^t X_{s-}dY_s + \int\limits_0^t Y_{s-}dX_s + \langle X,Y\rangle_t,$$ so you can write the covariance (or cross-variation) of these $X$ and $Y$ as $$\langle X,Y\rangle_t = X_tY_t - X_0Y_0 - \int\limits_0^t X_{s-}dY_s - \int\limits_0^t Y_{s-}dX_s.$$ Note that $(X,Y)\mapsto \langle X,Y\rangle$ is symmetric and bilinear, thus the polarization identity holds:

$\begin{aligned} \langle X+Y\rangle = \langle X+Y,X+Y\rangle &= \langle X,X\rangle+\langle X,Y\rangle+\langle Y,X\rangle+\langle Y,Y\rangle\\ &= \langle X,X\rangle + 2\langle X,Y\rangle+ \langle Y,Y\rangle \\ &= \langle X\rangle + 2\langle X,Y\rangle + \langle Y\rangle. \end{aligned}$

Having this form, lets check the claim. With $Z_t:=\langle X_t,Y_t\rangle$, $$X_tY_t - Z_t = -X_0Y_0 - \int\limits_0^t X_{s-}dY_s - \int\limits_0^t Y_{s-}dX_s,$$ is a local martingale. Now suppose that there is another such process $\tilde{Z}_t$ with finite variation. Then $Z_t - \tilde{Z}_t = X_tY_t - \tilde{Z}_t - (X_tY_t - Z_t)$ would be another local martingale with finite variation and $\triangle(Z_t-\tilde{Z}_t)=0$ almost surely, where $\triangle X_t:= X_t - X_{t-}$. $Z_t-\tilde{Z}_t$ is a continuous local martingale of finite variation, and thus $Z_t-\tilde{Z}_t = Z_0-\tilde{Z}_0=0$ almost surely. I.e. continuous local martingales of finite variation are almost surely constant.


Let $M'=XY-\langle X,Y\rangle$ be the martingale given by your definition. Let $M''=XY-A$ be another martingale for a process of the form $A=A^{(1)}-A^{(2)}$ for $A^{(j)}$ adapted and natural increasing.

Using now that $B=M'-M''=A-\langle X,Y\rangle$ is a martingale of bounded variation like in the proof of the uniqueness of the Doob-Meyer decomposition it follows that $B=0$ (up to distinguishability). In this part of the proof it is not required that $XY$ is a submartingale.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.